1999
DOI: 10.1099/0022-1317-80-7-1759
|View full text |Cite
|
Sign up to set email alerts
|

TT virus sequence heterogeneity in vivo: evidence for co-infection with multiple genetic types.

Abstract: TT virus (TTV) is a newly described DNA virus of humans that exhibits an unusually high degree of genetic heterogeneity. We have performed extensive analysis of the TTV populations present in samples, taken over a period of 2 to 6 years, from three individuals with persistent TTV infection. TTV DNA titres estimated for sequential samples were found to be quite stable over the entire study period in two patients, but fluctuated considerably in the third. DNA sequence analysis revealed different genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 34 publications
(42 reference statements)
10
63
0
Order By: Relevance
“…Subsequently, HCV viremia declined at a lower rate up to day 90, when the maximum proportion of patients who had cleared the virus to an undetectable level (67%) was also observed. In accord with previous findings (4,18), in four untreated patients, monthly measurement of TTV and HCV levels in plasma showed essentially stable values, with fluctuations of no more than 0.6 and 0.5 log 10 copies/ml, respectively (data not shown). Figure 1 shows the sequential modifications of plasma TTV levels of the patients for whom a minimum of six sequential samplings were available.…”
Section: Resultssupporting
confidence: 77%
“…Subsequently, HCV viremia declined at a lower rate up to day 90, when the maximum proportion of patients who had cleared the virus to an undetectable level (67%) was also observed. In accord with previous findings (4,18), in four untreated patients, monthly measurement of TTV and HCV levels in plasma showed essentially stable values, with fluctuations of no more than 0.6 and 0.5 log 10 copies/ml, respectively (data not shown). Figure 1 shows the sequential modifications of plasma TTV levels of the patients for whom a minimum of six sequential samplings were available.…”
Section: Resultssupporting
confidence: 77%
“…As pointed out by Okamoto et al (23), the extent of TTV diversity currently recognized is already unusually great for a DNA virus but is bound to increase substantially with the accumulation of sequence data worldwide. Importantly, detection of mixed populations of TTV belonging to more than one group (up to three groups) in a single subject was a frequent finding of this and previous studies (3,9,19,28) and represents a further indication of the ubiquity and heterogeneity of TTV infection. Recent data have shown that adults can harbor different mixtures of TTV genotypes in different organs, suggestive of a preferential tropism of certain TTV strains for specific tissues (8,23,24).…”
Section: Discussionmentioning
confidence: 81%
“…tissues [7,13]. Recently, a group of even more divergent viruses was discovered [14,15]; these viruses show a similar genome organisation to TTV but they are quite different in nucleotide sequence and genome length; the genome of these newly discovered viruses (described as TTV-like minivirus; TLMV) is almost 1000 bases shorter (2.9 kb).…”
Section: Genetic Diversitymentioning
confidence: 99%